2‐(Undecyloxy)‐ethanol is a major component of the male‐produced aggregation pheromone of Monochamus sutor. Issue 2 (27th August 2013) - Pajares, Juan A.; Álvarez, Gonzalo; Hall, David R.; Douglas, Paul; Centeno, Felix; Ibarra, Nieves; Schroeder, Martin; Teale, Stephen A.; Wang, Zhiying; Yan, Shanchun; Millar, Jocelyn G.; Hanks, Lawrence M.
Abstract The small white‐marmorated longicorn beetle, Monochamus sutor (L.) (Coleoptera: Cerambycidae), is widely distributed throughout Europe and Asia. It is a potential vector of the pine wood nematode, Bursaphelenchus xylophilus (Steiner et Buhrer) Nickle, the causal agent of the devastating pine wilt disease. Volatiles were collected from both male and female beetles after maturation feeding. In analyses of these collections using gas chromatography (GC) coupled to mass spectrometry, a single male‐specific compound was detected and identified as 2‐(undecyloxy)‐ethanol. In analyses by GC coupled to electroantennography the only consistent responses from both female and male antennae were to this compound. Trapping tests were carried out in Spain, Sweden, and China. 2‐(Undecyloxy)‐ethanol was attractive to both male and female M. sutor beetles. A blend of the bark beetle pheromones ipsenol, ipsdienol, and 2‐methyl‐3‐buten‐2‐ol was also attractive to both sexes in Spain and Sweden, and further increased the attractiveness of the 2‐(undecyloxy)‐ethanol. The host plant volatiles α‐pinene, 3‐carene, and ethanol were weakly attractive, if at all, in all three countries and did not significantly increase the attractiveness of the blend of 2‐(undecyloxy)‐ethanol and bark beetle pheromones. 2‐(Undecyloxy)‐ethanol is thus proposed to be the major, if not only, component of the male‐produced aggregation pheromone of M. sutor, and its role is discussed. This compound has been reported as a pheromone of several other Monochamus species and is another example of the parsimony that seems to exist among the pheromones of many of the Cerambycidae. Traps baited with 2‐(undecyloxy)‐ethanol and bark beetle pheromones should be useful for monitoring and control of pine wilt disease, should M. sutor be proven to be a vector of the nematode.